ALGAE AS BIOINDICATORS FOR ASSESSMENT AND MONITORING THE WATER QUALITY WITH SPECIAL REFERENCE TO DUHOK’S DRINKING WATER PLANT - SULAIMAN, AHMED WAADALLAH; RAOOF, EZAT YOUSIF (Journal of Duhok University, 2023)
The physical, chemical, and biological parameters have been studied at six selected sampling sites in the Duhok Drinking water plant within Duhok city. Algal and water samples were collected monthly from October 2021 to September 2022. The water temperature ranged from 8.1 to 22.5 0C. The pH values varied from 7.31 to 8.93. Specific electrical conductivity ranged from 328.1 to 472.6 µs cm-1. Alkalinity values ranged from 120 to 195 mg/L CaCO3. Total hardness varied from 184 to 250 mg/L CaCO3. Silicate values ranged from 67.89 to 120.01 mg/L. Phosphate concentrations ranged from 0.01 to 0.73 mg/L. Values of nitrate varied from 2.3 to 5.8 mg/L. A total of 58 algal taxa were identified during this study, which belong to four divisions: 25 taxa belong to Bacillariophyta, making up 43% from the all; 21 taxa belong to Chlorophyta, making up 36% from the all; 7 taxa belong to Cyanophyta, making up 12% from the all; and 2 taxa belong to Euglenophyta, making up 3.5%. 2 taxa belong to Dinoflagellata, making up 3.5% from the all; 1 taxa belong to Xanthophyta, making up 2% from the all